Atorvastatin treatment improves effects of implanted mesenchymal stem cells: meta-analysis of animal models with acute myocardial infarction. Issue 1 (December 2015) - Dai, Guo; Xu, Qing; Luo, Rong; Gao, Jianfang; Chen, Hui; Deng, Yun; Li, Yongqing; Wang, Yuequn; Yuan, Wuzhou; Wu, Xiushan
Abstract Background Previous studies reported that Atorvastatin (ATOR) can improve the efficacy of Mesenchymal stem cells (MSCs) transplantation after acute myocardial infarction (AMI). However, the results of those studies were inconsistent. To clarify the beneficial effects of atorvastatin added to the cell therapy with MSCs in animal model of acute myocardial infarction (AMI), we performed a systematic review and meta-analysis of case–control studies. Methods Searches were performed using the PubMed database, the Excerpta Medica Database (Embase), the Science Citation Index, the China National Knowledge Information database, the Wanfang database, and the Chinese Scientific and Technological Journal Database (VIP database). The search term included "Atorvastatin (or Ator)", "Mesenchymal Stem Cells (or Mesenchymal Stem Cell or MSC or MSCs)" and "Acute Myocardial Infarction (or Myocardial Infarction or AMI or MI)". The endpoints were the left ventricular ejection fraction (LVEF) in animal model with AMI. Results In total, 5 studies were included in the meta-analysis. Pooled analysis indicated a significant LVEF difference at 4 weeks follow-up between MSCs + ATOR combine group and MSCs alone group (95 % CI, 9.09–13.62 %;P  < 0.01) with heterogeneity (P  = 0.28;P >0.05) and inconsistency (I2 : 22 %). Conclusions Atorvastatin can enhance the existing effects of MSCs transplantation, and this combinational therapy is a superior cell/pharmacological therapeutic approach that merits future preclinical and clinical studies.